Kegiatan Pengabdian Kepada Masyrakat (PKM) : Edukasi dan Pembiasaan Cuci Tangan Pakai Sabun (CTPS) dengan Benar Guna Menjaga Kesehatan pada Anak TK Darma Wanita Persatuan Sidodadi, Taman, Sidoarjo - Utami Puji Lestari; Nurul Agustin; Indah Mufidah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Early childhood health is an important aspect that must be maintained consistently, especially in preventing the spread of infectious diseases. One simple but effective way to maintain health is through the habit of washing hands with soap (CTPS) properly. This Community Service (PKM) activity aims to provide education and familiarize children with the correct CTPS behavior at Darma Wanita Persatuan Sidodadi Kindergarten, Taman District, Sidoarjo Regency. The methods used in this activity include interactive counseling, explanation of how to wash hands properly based on WHO steps, and direct practice involving children and teachers. The results of the activity showed an increase in children's understanding of the importance of washing hands and skills in doing CTPS properly. It is hoped that this habit can be continued by the school and parents as part of preventive efforts in maintaining children's health.